Design and characterization of chionodracine-derived antimicrobial peptides with enhanced activity against drug-resistant human pathogens. Issue 72 (12th December 2018) - Olivieri, Cristina; Bugli, Francesca; Menchinelli, Giulia; Veglia, Gianluigi; Buonocore, Francesco; Scapigliati, Giuseppe; Stocchi, Valentina; Ceccacci, Francesca; Papi, Massimiliano; Sanguinetti, Maurizio; Porcelli, Fernando
Abstract : Design of new chionodracine-derived peptides with potent activity against drug-resistant human pathogens. Abstract : Starting from the sequence of the amphipathic α-helix of chionodracine (Cnd, 22 amino acids), we designed a series of mutants to increase Cnd's antimicrobial activity and selectivity toward prokaryotic cells and drug-resistant bacterial pathogens. We characterized these new Cnd-derived peptides using fluorescence, CD spectroscopy, and transmission electron microscopy, studying their interactions with synthetic lipid vesicles and assaying their biological function against E. faecium, S. aureus, K. pneumoniae, A. baumannii, P. aeruginosa, and Enterobacter sp. Upon interaction with model membranes, these new peptides with higher net charges and hydrophobic moments adopt a helical conformation similar to Cnd. Notably, they display a low cytotoxic activity against human primary cells, a low hemolytic activity, but a significantly high bactericidal activity against drug-resistant bacterial pathogens. The low values of micromolar minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) make these Cnd-derived peptides potential templates to develop antimicrobial agents against drug-resistant human pathogens.